The Effect Of Halal Tourism On Millenial Tourist Satisfaction In Sabang Island As Tourism Object - Mutia Arda; Dewi Andriany (Proceeding International Seminar of Islamic Studies, 2019)
The increasing influence of technology and the desire to travel around the world are some of the factors driving the growth of the young Muslim tourist market. This young tourist is also called millennial tourists. Tourism for millennials is growing rapidly with greater income. Tourist satisfaction with tourist destinations is related to travel experiences consisting of accommodation, weather, natural environment, social environment and others. The city of Sabang in the province of Aceh is one of the locations of halal attractions which are in great demand by local and foreign tourists. The purpose of this study is to analyze the influence of halal tourism on millennial satisfaction. The population of this study is millennial tourists who become followers of Instagram account @ Sabangtrip. The sampling technique used is nonprobability sampling. The population in this study is not clearly known, so the type of sampling used is purposive sampling which is taking the subject of research based on the criterias. The Lemeshow formula is used for unknown populations, so the sample in this study was 98 people. The analysis technique used is simple linear regression analysis. The partial and simultaneous test results show that halal tourism has a positive and significant effect on millennial satisfaction. Based on the results of the study it was found that halal tourism gave a variation on millennial satisfaction by 86%.